VD_FINDINFO AP / 2011 / 107 vom 8. Juni 2011 - VD Tribunal cantonal (2011)
APPRÉCIATION DES PREUVES, RÉSILIATION, ÉCOLE PRIVÉE, MANDAT, JUGEMENT PAR DÉFAUT | 394 al. 2 CO, 308 al. 1 CPC, 308 al. 2 CPC, 457 CPC